ANALISI S YURIDIS PENUNTUTAN PENGEMBALIAN MAHAR AKIBAT PERCERAIAN (PUTUSAN MAHKAMAH SYAR’IYAH ACEH NOMOR: 15/PDT.G/2011/MS-ACEH) - YANTI JULIA (PREMISE LAW JURNAL, 2014)
ABSTRACT Divorce occurs, it will cause legal consequence on those who are related to a household. The husband or the wife who feels inconvenient will claim his/her rights such as the right to bring up the child, to divide joint property, and sometimes to claim the return of dowry to the ex-wifeThe obligation to pay for a dowry is based on some reasons: judicial reason can be seen in the Koran, An-Nisa:4, 20, 24, and 25, Al-Hadis, Ijtihat, and in KHI (the Compilation of Islamic Laws) it is regulated in Article 30; it can also viewed from historical reason, philosophical reason, and sociological reason. In the Islamic law, a dowry which has been given to a future wife will belong to her and cannot be claimed anymore. Nevertheless, a dowry can be claimed by the ex-husband if the divorce is without any reason and in the request of and the fault of the ex-wife. Panel of judges also consider that the return of the dowry because of a divorce is the form of justice for a husband who is claimed for a divorce by his wife without any reason. Keywords: Judicial Analysis, Divorce, Dowry